A blockchain-based interactive approach between digital twin-based manufacturing systems. (January 2023) - Liu, Shimin; Lu, Yuqian; Li, Jie; Shen, Xingwang; Sun, Xuemin; Bao, Jinsong
Highlights: Blockchain-based data exchange method can reduce the pressure on the enterprise cloud. Blockchain-based can improve the data interaction efficiency by a discrete organizational form. The edge pools can be connected adaptively according to the dynamic manufacturing tasks. Abstract: Cloud manufacturing provides an interactive environment for collaboration between digital twin-based manufacturing systems. However, access to the enterprise cloud by a significant number of digital twin systems would lead to bandwidth competition and severe delays. Therefore, the data exchange process needs to be improved in a more reliable and effective way. To tackle this issue, a blockchain-based data interactive approach is proposed to form the peer-to-peer data exchange mechanism between digital twin-based manufacturing systems. First, the manufacturing edge pool is developed given specific manufacturing tasks. The blockchain enables the digital twin manufacturing systems to exchange data effectively and safely. Besides, the application of the blockchain reduces the dependencies of the digital twin systems on the enterprise cloud and improves the flexibility of the workshops. Finally, the effectiveness of this method is verified by a case study on the engine.